Distribution, metabolism, excretion, and toxicity of implanted silver: a review. (3rd September 2022) - Hadrup, Niels; Sharma, Anoop K.; Jacobsen, Nicklas R.; Loeschner, Katrin
Abstract: Some implantable medical devices contain silver. We aimed to assess at what amount implanted silver becomes toxic. Silver was elevated in bodily fluids and tissues surrounding silver-containing implants. Silver released from implants also distributes to blood and other tissues; there is evidence to suggest silver can pass the blood-brain-barrier. Silver can be deposited as nano-sized particles in various tissues. Such particles, in addition to silver, often contain other elements too, e.g., selenium and sulfur. Silver released from implants seems to stay in the body for long periods (years). Reported excretion pathways following implantation are urinary and fecal ones. Reported toxicological effects were virtually all local reactions surrounding the implants. Argyria is a blue-gray discoloration of the skin due to deposited silver granules. Localized argyria has been described after the implantation of acupuncture needles and silver-coated prostheses, although the presence of silver was tested only for and shown in the former. Other toxicological effects include local tissue reactivity and examples of neurotoxic and vascular effects. We did not include genotoxicity studies in the present publication as we recently evaluated silver to be genotoxic. Carcinogenicity studies were absent. We conclude that local toxicity of implanted silver can be foreseen in some situations.